1999
DOI: 10.1046/j.1365-2230.1999.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated immunity to Malassezia furfur in patients with seborrhoeic dermatitis and pityriasis versicolor

Abstract: The lymphocyte transformation response to Malassezia furfur, Candida albicans, phytohaemagglutinin, concanavlin A and tuberculin purified protein derivative of 12 patients with pityriasis versicolor, 15 patients with seborrhoeic dermatitis and matched controls, was studied. Patients with pityriasis versicolor showed a significantly lower response to M. furfur than patients with seborrhoeic dermatitis and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 23 publications
1
11
0
4
Order By: Relevance
“…The most recent study of cellular immunity in SD also did not show any difference in response between patients and controls to Malassezia or mitogens (46).…”
Section: Cellular Immune Responsesmentioning
confidence: 85%
See 1 more Smart Citation
“…The most recent study of cellular immunity in SD also did not show any difference in response between patients and controls to Malassezia or mitogens (46).…”
Section: Cellular Immune Responsesmentioning
confidence: 85%
“…Recently, Bergbrant et al (46) reported significantly lower LT responses to Malassezia in patients with PV than in controls (P Ͻ 0.001), but the responses to mitogens did not differ between the two groups.…”
Section: Pityriasis Versicolormentioning
confidence: 93%
“…and inflammation. Indeed, the yeasts are responsible for a superficial subclinical micro-inflammation in dandruff and a similar although more pronounced reaction in seborrhoeic dermatitis [23, 24, 25, 26]. KET which exhibits a strong anti- Malassezia effect may therefore show an indirect mild anti-inflammatory effect in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Berger and Greene in 1991 [33] reported that this condition could be a hypersensitivity reaction to Pityrosporum yeasts, but its association is still doubtful (Figure 1). However, recent studies have failed to demonstrate any fungal overgrowth [34] or a rise in the levels of IgG titers against the yeast in HIV-1-seropositive patients [35,36]. …”
Section: Reviewmentioning
confidence: 99%